Weekly paclitaxel, carboplatin, cetuximab, and cetuximab, docetaxel, cisplatin, and fluorouracil, followed by local therapy in previously untreated, locally advanced head and neck squamous cell carcinoma. (31st December 2018) - Haddad, R I; Massarelli, E; Lee, J J; Lin, H Y; Hutcheson, K; Lewis, J; Garden, A S; Blumenschein, G R; William, W N; Pharaon, R R; Tishler, R B; Glisson, B S; et al.
Abstract: Background: The survival advantage of induction chemotherapy (IC) followed by locoregional treatment is controversial in locally advanced head and neck squamous cell carcinoma (LAHNSCC). We previously showed feasibility and safety of cetuximab-based IC (paclitaxel/carboplatin/cetuximab—PCC, and docetaxel/cisplatin/5-fluorouracil/cetuximab—C-TPF) followed by local therapy in LAHNSCC. The primary end point of this phase II clinical trial with randomization to PCC and C-TPF followed by combined local therapy in patients with LAHNSCC stratified by human papillomavirus (HPV) status and T-stage was 2-year progression-free survival (PFS) compared with historical control. Patients and methods: Eligible patients were ≥18 years with squamous cell carcinoma of the oropharynx, oral cavity, nasopharynx, hypopharynx, or larynx with measurable stage IV (T0–4N2b–2c/3M0) and known HPV by p16 status. Stratification was by HPV and T-stage into one of the two risk groups: (i) low-risk: HPV-positive and T0–3 or HPV-negative and T0–2; (ii) intermediate/high-risk: HPV-positive and T4 or HPV-negative and T3–4. Patient reported outcomes were carried out. Results: A total of 136 patients were randomized in the study, 68 to each arm. With a median follow up of 3.2 years, the 2-year PFS in the PCC arm was 89% in the overall, 96% in the low-risk and 67% in the intermediate/high-risk groups; in the C-TPF arm 2-year PFS was 88% in the overall, 88% in the low-risk and 89% in the intermediate/high-risk groups. Conclusion: The observed 2-year PFS of PCC in the low-risk group and of C-TPF in the intermediate/high-risk group showed a 20% improvement compared with the historical control derived from RTOG-0129, therefore reaching the primary end point of the trial.